2004
DOI: 10.2307/20159599
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer Through Inheritance: Spin-Out Generation, Development, and Survival.

Abstract: We investigated how the knowledge capabilities of industry incumbents affected the generation, development, and performance of "spin-outs" (entrepreneurial ventures of ex-employees). Analyses of 1977-97 data from the disk drive industry supported our hypothesis that incumbents with both strong technological and market pioneering know-how generate fewer spin-outs than firms with strength in only one of these areas. Also, an incumbent's capabilities at the time of a spin-out's founding positively affect the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
735
5
44

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 778 publications
(806 citation statements)
references
References 137 publications
(81 reference statements)
22
735
5
44
Order By: Relevance
“…Furthermore, a major number of entries in knowledge-intensive or technology-intensive industries could be the result of spin-offs from existing firms, an example of employee mobility and knowledge diffusion. Especially, firms with an abundant amount of underexploited knowledge act as seedbed for spin-offs (Agarwal et al, 2004) and are a playground for new founders (Franco and Filson, 2000).…”
Section: Discussion and Possible Policy Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a major number of entries in knowledge-intensive or technology-intensive industries could be the result of spin-offs from existing firms, an example of employee mobility and knowledge diffusion. Especially, firms with an abundant amount of underexploited knowledge act as seedbed for spin-offs (Agarwal et al, 2004) and are a playground for new founders (Franco and Filson, 2000).…”
Section: Discussion and Possible Policy Implicationsmentioning
confidence: 99%
“…Christensen (1993) analyzed entry in the U.S. disk drive industry between 1976 and 1989; he found that spin-offs were more successful in surviving and that they generated more revenues than the nonspin-off entrants. Agarwal et al (2004) found that higher technological know-how positively affects the survival chance of entrants in the disk drive industry between 1977 and 1997.…”
Section: Knowledge Entrepreneurial Opportunities and Their Impact Onmentioning
confidence: 99%
See 2 more Smart Citations
“…Industries with highly successful spin-offs include historical cases such as automobiles (Klepper, 2002) and tires (Buenstorf and Klepper, 2005), but also modern high-tech industries such as semiconductors (Moore and Davis, 2004), disk drives (Agarwal et al, 2004), and lasers (Buenstorf, 2005;Klepper and Sleeper, 2005). Not all spinoffs perform equally well, but the top performers are concentrated among the spin-offs of leading incumbent firms.…”
Section: Industry Evolution and Entrepreneurial Opportunitiesmentioning
confidence: 99%